PROFIL KEHIDUPAN PEDAGANG KAKI LIMA DI JL.HR SOEBRANTAS KECAMATAN TAMPAN KOTA PEKANBARU - Marcelina Alfanda R.L; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Pedagang kaki lima is a person who trades using a cart or spreads his merchandise on the side of a road or sidewalk in a city street. The objectives discussed in this study are (1) to determine the types and characteristics of pedagang kaki lima and (2) what factors cause pedagang kaki lima to survive in JL.HR.Soebrantas, Tampan District, Pekanbaru City. The method used in this study is a qualitative research method with data collection techniques carried out through observation, interviews and documentation. The subjects in this study were pedagang kaki lima in JL.HR.Soebrantas, Tampan District, Pekanbaru City. The informant research was conducted by using purposive sampling technique as many as 8 informants based on certain criteria or limitations. From the research results it can be concluded that from the socioeconomic background in terms of income, pedagang kaki lima are classified as medium and they are able to produce materials to meet family needs by selling various types of merchandise, ranging from food, drinks, clothes and accessories. Pedagang kaki lima survive due to the necessity factors as well as limitations and work opportunities in the area of origin so that the existence of pedagang kaki lima is a solution in reducing unemployment. Keywords: pedagang kaki lima, types andcharacteristics of pedagang kaki lima